Cost effective energy and CO2 emissions optimization in building renovation annex 56 methodology and its application to a case study - Almeida, Manuela Guedes de (2016)
Following the impact of the climate changes and their causes, buildings proved to be one of the main responsible for the greenhouse effect due to the carbon emissions related with their construction and use. The recent changes in the European regulations, in a tentative to improve buildings energy performance, are mostly suited to new buildings. However, the majority of the building stock has more than twenty years and renovating it, in accordance with the current standards, can lead to difficult and expensive procedures. Considering the main goals of reducing the use of fossil fuels and the related emissions, the use of renewable energy sources offers an alternative to these deep interventions in the buildings envelope. In a search for the right balance between energy conservation and energy efficiency measures and technologies that require the use of renewable energy, IEA EBC launched Annex 56. The main purpose of the project is the development of a methodological framework that allows comparing renovation scenarios that deeply reduce energy and carbon emissions combining energy efficiency measures and the use of renewable energy. It takes into consideration not only the reduction of the energy use, carbon emissions reductions and costs, but also embodied energy and co-benefits that arise from the renovation procedure. The methodology was applied to a Portuguese case-study that has gone under renovation. The results allow comparing the chosen renovation scenario with other scenarios and justify the option of going beyond the cost optimal solutions in order to have more effective reduction of the carbon emission while still being cost effective.